NMR study of the anisotropic transport properties of uniaxially stretched membranes for fuel cells - Klein, Mathieu; Perrin, Jean-Christophe; Leclerc, Sébastien; Guendouz, Laouès; Lottin, Olivier; Dillet, Jérôme (Diffusion Fundamentals, 2013)
We used NMR techniques to probe the anisotropic properties of stretched Nafion®115membranes. The alignment of the polymeric structure under a uniaxial load is at the origin of a strong anisotropy of both the water self-diffusion coefficient and the proton conductivity. The determination of these two important membrane properties may lead to new fundamental information on the nature of the proton transport mechanisms in such oriented weaklycharged systems.